Warranty and its effect towards customer satisfaction in Malaysia’s electronic industry / Mohd Rizaimy Shaharudin... [et al.] - Shaharudin, Mohd Rizaimy; Wan Omar, Maznah; Abu Hassan, Anita; Azyyati, Anuar (Universiti Teknologi MARA, Kedah, 2011)
This study aims to determine the factors affecting customer satisfaction inafter-sales service. It helps to extend the understanding on warranty and its influence towards customers’ satisfaction, an important element in retaining a profitable business relationship with the customer. To date, there have been very minimal studies conducted on the after-sales service in business organizations particularly the electronic industry in Malaysia. Therefore, from the data presented in this study, it can be expected that the findings can benefit both the industrial community and the academia by giving a new source of ideas and information. Results indicated to confirm on the earlier literature that there was a strong relationship between warranty and customer satisfaction in either the consumer or the business market environment. Future research should focus on the similar study of factors affecting customer satisfaction in after-sales service in other prominent industries such as automotive, construction and other manufacturing as well as service sectors.